Caminhos e sentidos da política de educação: uma avaliação do modelo de gestão para resultados implementado no âmbito da Secretaria da Educação do Ceará - Soares, Francisca Juliana Feitosa (2022)
This research aims to assess how the dimensions of the Management for Results model are manifested in the actions of the educational policy from the Ceará’s State Government’s Department of Education, taking into account the instances, planning, monitoring, and budget, particularly between 2016 to 2019. The relevance of this theme arises from the fact that contemporary reforms have been increasing in evidence in discussions about modernizing public management in Brazil. In this context, the State Government, aiming to improve its efficiency and consonant with recent State reforms, adopted the MfR model. For a long time, the rhetoric of managerialism has echoed in public policies in general. From this understanding, this study aims to pose the following question: By adopting the MfR’s management model, what is its resulting impact on the educational policies’ actions? For that, this evaluative research is composed of a comprehensive analysis and is based on the counter-hegemonic perspective and on the experiential method of merging between text and context for public policies investigation from Raul Lejano (2012). From this perspective, this research has a qualitative character and a descriptive and documental nature, for we sought a series of information about MfR to understand the phenomenon and the reality of the State Government’s case. Moreover, we conducted semi-structured interviews with public managers involved and the other members linked to the MfR model’s implementation, as well as participant observation to capture the institution’s working dynamics and the perspectives of public managers and other professionals directly involved in the construction of the results agreement object. This research is a case study having the Department of Education as a locus. We also note that this study holds a meta-evaluation in its essence, which can be seen through the indicators, goals, and priority projects in the Results Agreement document from the Department of Education. For the data gathering and analysis, we used method triangulation to understand the phenomenon from several dimensions. From the research results, we observe that tensions surround the educational field. By the data triangulation conducted, we see that the neoliberal context, allied to the spread of a Minimum State ideal, the reform, and modernization of structure are strong inducers of the educational policies, as seen with the influence of multilateral organizations on the prioritization by means to fulfill the goals of the so-called global agendas. Another aspect understood from the conducted interviews is that the educational policies already shared a significant part of the workings of public management with results as a primary goal. In addition, we noticed weaknesses in the agreement document, present in its indicators and evaluation and monitoring instruments.